2023
DOI: 10.17219/dmp/153916
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial species and factors influencing the contamination of the inner and outer layers of face masks used in dentistry

Dong-Eun Lee

Abstract: Background. Many patients are clinically consulted in dental clinics, where aerosol-generating procedures are widely used. In our previous study, we evaluated the temperature, humidity and contamination rates on the inner layer of masks according to the mask-wearing time. However, it is important to assess the contamination rates on the outer layer of masks used in dentistry as well. Previously, while examining the contamination rates, we only identified the associated bacteria; no detailed analysis of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These findings revealed that the internal and external strata of the masks were found to contain 3.3 × 10 8 and 8.5 × 10 8 colony-forming units, correspondingly. Moreover, the infectivity proportions of the masks demonstrated an upward trend in tandem with the duration of mask-wearing [25].…”
Section: Discussionmentioning
confidence: 96%
“…These findings revealed that the internal and external strata of the masks were found to contain 3.3 × 10 8 and 8.5 × 10 8 colony-forming units, correspondingly. Moreover, the infectivity proportions of the masks demonstrated an upward trend in tandem with the duration of mask-wearing [25].…”
Section: Discussionmentioning
confidence: 96%